2021
DOI: 10.1111/epi.16850
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of epilepsy in Latin America and the Caribbean: A systematic review and meta‐analysis of population‐based studies

Abstract: Objective This study was undertaken to perform an updated systematic review and meta‐analysis to estimate the pooled prevalence and incidence of epilepsy in Latin America and the Caribbean (LAC), describing trends over time, and exploring potential clinical and epidemiological factors explaining the heterogeneity in the region. Methods Observational studies assessing the incidence or prevalence of epilepsy in LAC countries up to March 2020 were systematically reviewed according to PRISMA (Preferred Reporting I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 62 publications
5
31
3
Order By: Relevance
“…A change in seizure threshold among recipients of mRNA vaccines has not been observed in RCTs, and, according to our data, this is unlikely; it is possible that structural (e.g., pre-existing epilepsy) or pathological conditions (e.g., concomitant COVID-19) may explain most of the reported seizures. While vaccines may increase the frequency of febrile seizures in children, in most cases, the coexistence of structural or genetic causes explains epileptic seizures [ [17] , [18] , [19] ]. The temporal association of seizures with inactivated and live attenuated viral vaccines is well known but infrequent [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in seizure threshold among recipients of mRNA vaccines has not been observed in RCTs, and, according to our data, this is unlikely; it is possible that structural (e.g., pre-existing epilepsy) or pathological conditions (e.g., concomitant COVID-19) may explain most of the reported seizures. While vaccines may increase the frequency of febrile seizures in children, in most cases, the coexistence of structural or genetic causes explains epileptic seizures [ [17] , [18] , [19] ]. The temporal association of seizures with inactivated and live attenuated viral vaccines is well known but infrequent [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The temporal association of seizures with inactivated and live attenuated viral vaccines is well known but infrequent [ 17 ]. The calculated lifetime prevalence of epilepsy in Latin America is 14.9/1000 inhabitants [ 19 ]. A similar prevalence is expected in our cohort, where only a handful of epileptic seizures occurred, suggesting that mRNA vaccines are not associated with a higher frequency of new-onset seizures, and are safe even among those with a history of seizures/epilepsy (~1.5% of those immunized).…”
Section: Discussionmentioning
confidence: 99%
“…The certain of evidence assessment was conducted as in our previously published articles [ 2 , 65 , 99 ]. We adapted the evaluation for prevalence meta-analysis using the five domains described in the GRADE handbook as follows: study limitations (the risk of bias of the primary studies), imprecision (appropriateness of the sample size and width of the CI), indirectness (generalizability of results), inconsistency (between-study heterogeneity), and publication bias [ 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…7 By contrast, an international metaanalysis calculated a prevalence of 0.64% 8 and a recent Latin America systematic review and meta-analysis found an active prevalence of 0.9%. 9 Although rates may indeed differ among different populations, a major problem is the wide variation in the completeness of case ascertainment and the definitions of epilepsy used in studies on the epidemiology of epilepsy. If the Spanish prevalence is actually higher, then the cumulative incidence of epilepsy patients with COVID-19 is probably not statistically different from the control population.…”
Section: Epilepsy Currents 1-3mentioning
confidence: 99%